The Effectiveness of Using Pictemp (Picture Template) to Aid Year 3 Vocabulary Skill in Malaysia - Md Dali, Naqib Hanis; Saigaran, Turkasshini Raja; Md Yunus, Melor (Universitas Sebelas Maret, 2018)
Malaysian Government English Language Policy had clearly stated; English Language must be taught to all Malaysian student as a second language. The action research aimed to study the extent to which using the PicTemp (picture template) method is effective in improving the vocabulary among Year 3 pupils. The research participants comprised 10 low achievers Year 3 pupils from primary school located in Sepang and Putrajaya, Malaysia. The study involved the use of two different teaching methods, which were the traditional method and PicTemp methods. The instruments for the study consisted of Test 1 and Test 2, an interview schedule as well as journal entries. The results of the study showed that the PicTemp method was effective in helping Year 3 pupils develop their vocabulary. Although the results were positive, the study also finds that PicTemp method to be exhausting for young learners. Hence the study suggests that the application of this method could be on weekly basis.